The Role of Locus of Control as a Mediation of Financial Literacy and Financial Inclusion on The Financial Performance of MSMEs - Ni Wayan Novi Budiasni; Ni Made Sri Ayuni (University of Merdeka Malang, 2022)
This study examines the relationship between financial literacy and financial inclusion of MSMEs' financial performance in Buleleng Regency, where the locus of control variables are intervening variables. This phenomenon is essential to be studied given the condition of the performance of MSMEs in the Buleleng Regency, which is not optimal, and the importance of the MSME sector to improve the national economy. This research was conducted using quantitative methods and data analysis techniques using SEM (Structural Equation Modeling) with the PLS (Partial Least Square) method. The processed sample is 100 MSMEs samples with the Slovin formula determined by the random sampling technique. The test results show that the locus of control can intervene variables between financial literacy and financial inclusion of MSME's financial performance in Buleleng Regency with a positive and significant influence. These results reinforce that the Locus of Control has an important role in supporting the influence between financial literacy and financial inclusion on the financial performance of MSMEs in the Buleleng Regency.